Prison Leave in Denmark: How a Tradition of Combining Rehabilitation with Discipline Developed into Putting Access to Justice at Risk - Storgaard, Anette (European journal on criminal policy and research, 2020)
The motivation for prison leave in the Danish penal system is based on two rationales: humanity, because the maintenance of positive contacts outside prison is expected to further a future life without crime; and discipline, because the risk of being discredited and missing out on prison leave is expected to have an effect on prisoners’ compliance with the rules in prison. The Corrections Act contains certain framework provisions. The detailed regulation of prison leave is found within separate rules and guidelines. The power to make day-to-day decisions concerning the permission or revocation of prison leave lies in the hands of the prison administration. The regulation of prison leave and release on parole are interrelated, as the latter more or less directly depends on a successful period of regular prison leave. The total amount of prison leave is declining. Over the last few decades, more prison leaves have been granted for occasional reasons, such as being seen by a doctor, rather than oriented in preparation for release, such as to attend to job or education. It is argued that the decline in the total amount of prison leave and the increase in the total number of rejections of parole are directly and indirectly interrelated. It is further argued that political intervention in the well-established division of power between legislation and discretionary power jeopardizes transparency in decision-making and puts access to justice for prisoners at risk.